Predictive Value of STC2 Gene Expression in Chemotherapy Response in Breast Cancer - Juan P. Muñoz; Nicolás Lampe-Huenul (Pharmaceuticals)
Background: Breast cancer is the most commonly diagnosed cancer among women, and resistance to chemotherapy presents a significant challenge in its treatment. Stanniocalcin-2 (STC2), a glycoprotein involved in calcium homeostasis and cellular stress responses, is frequently overexpressed in various human cancers. Despite its critical role in cellular adaptation to stress, the potential of STC2 as a biomarker for predicting chemotherapy response has not been evaluated. This study aimed to assess the potential of STC2 as a predictive biomarker of response to chemotherapy in breast cancer. Methods: We utilized publicly available databases to characterize STC2 expression in breast cancer patients and its role in predicting relapse-free survival (RFS). Moreover, we evaluated the treatment responses of patients subjected to chemotherapy, correlating their outcomes with STC2 expression levels to determine its potential as a predictive biomarker. Finally, we evaluated the STC2 expression levels in breast cancer cell lines following exposure to doxorubicin (Dox), the primary anthracycline used in chemotherapy, and they were contrasted with the publicly available dataset. Results: The analysis showed that STC2 is significantly overexpressed in luminal A breast cancer, where it is linked to genetic amplifications. High STC2 expression was associated with improved RFS in ER-positive patients but correlated with worse outcomes in ER-negative cases. Furthermore, in grade II ER-positive patients, higher STC2 expression is linked to better chemotherapy response, while in grade II ER-negative patients, it was associated with poorer response. Finally, STC2 downregulation was observed in response to Dox treatment. Conclusions: These findings suggest that STC2 expression serves as a predictive biomarker for chemotherapy response in grade II breast cancer patients.